Islamic Religious Education Learning Outcomes Evaluation: Implementation of Steps, Concepts and Solutions in Public Elementary School - Adiyono Adiyono; Awalina Fadhilatunnisa; Nofri Ahmadi Rahmat; Nurul Munawarroh (AL-ISHLAH: Jurnal Pendidikan, 2023)
Evaluation activities can be employed as a means to optimise the attainment of learning objectives and learning outcomes.   Understanding student performance as a foundation for fostering student potential.   This study focuses on the implementation of the evaluation of Islamic Education (PAI) learning outcomes, encompassing the planning process, objectives, types, and implementation strategies. It also examines the challenges faced by educators during the implementation and proposes potential solutions. This qualitative study acquired data through interviews and literature review. Data collection is the initial and essential stage in a study. The researchers employ various data collection approaches.   Researchers performed a question-and-answer session with the PAI Teacher at a public elementary school in Kuaro. In field research, narratives or accounts of heard and felt occurrences are analysed in detail to remain natural and accurately depict field phenomena. Planning for PAI learning outcome evaluation, including setting clear goals, identifying components, selecting procedures, collecting data, confirming data, and constructing assessment measuring instruments. Evaluation types: formative and summative. Evaluation methods—tests and non-tests. Evaluation limitations, short study hours, and poor infrastructure. According to the research above, PAI learning outcome evaluations are implemented using prior evaluation planning to maximise efficiency and effectiveness. PAI learning outcomes are evaluated utilising cognitive, emotional, and psychomotor assessments.